Identifying the audit committee financial expert - Puat Nelson, Sherliza; Devi, S. Susela (2008)
In light with the Section 407 of Sarbanes Oxley Act 2002, the audit committee’s role has become a daunting task to hold on to. More prominent responsibilities were put up before them, and especially for firms to identify their financial experts among their audit committee members. Prior literature also shows that there are associations in relation to market performance and earnings quality, if there exist an audit committee with an expertise in financial or accounting in the company. In Malaysia, the mandatory disclosure of naming their financial expert is still far. But, existing requirements do ask for companies to include among the audit committee members, at least one with an accounting or finance background, and, or with a professional accounting qualification. Still, there is insufficient guidance as to how we could identify if someone could be the potential audit committee financial expert. The existing paper intends to look into what it takes to be an audit committee financial expert. Three elements or basis were found from prior literature to form the basis of an expert; experiences, qualification and understanding of financial reporting.